Comparison of equilibrium techniques for the viscosity calculation from DPD simulations. Issue 36 (25th August 2021) - Panoukidou, Maria; Wand, Charlie R.; Carbone, Paola
Abstract : Revised Einstein–Helfand and revised Green–Kubo relations accurately predict viscosity trend with polymer length in DPD simulations. Abstract : Dissipative Particle Dynamics (DPD) is a powerful mesoscopic modelling technique that is routinely used to predict complex fluid morphology and structural properties. While its ability to quickly scan the conformational space is well known, it is unclear if DPD can correctly calculate the viscosity of complex fluids. In this work, we estimate the viscosity of several unentangled polymer solutions using both the Einstein and Green–Kubo formulas. For this purpose, an Einstein relation is derived analogous to the revised Green–Kubo formula suggested by Jung and Schmid, J. Chem. Phys., 2016, 144, 204104. We show that the DPD simulations reproduce the dynamical behaviour predicted by the theory irrespectively of the values of the conservative and friction parameters used and estimate a Schmidt number compatible to that of a fluid system. Moreover, we observe that the Einstein method requires shorter trajectories to achieve the same statistical accuracy as the Green–Kubo formula. This work shows that DPD can confidently be used to calculate the viscosity of complex fluids and that the statistical accuracy of short trajectories can be improved by using our revised Einstein formula.